Print v. electronic reference sources: Implications of an Australian study - Ritchie, A.; Genoni, Paul (Emerald Group Publishing Limited, 2007)
Purpose: The purpose of this paper is to explore the evolving balance between the use of print and electronic sources for answering reference questions. Design/methodology/approach: A review of the international literature from the mid‐1990s is conducted. A case study of reference questions received at the Northern Territory Library is undertaken, by auditing data held in the online reference information management system, RefTracker. Over 620 questions are categorised according to the sources used in responding to those questions. Findings: Results indicate that print and electronic sources are both important to the reference service at the Northern Territory Library. Research limitations/implications: There is great difficulty in assessing what constitutes a “correct” balance between print and electronic sources for responding to reference questions, and the current practice is likely to differ significantly between libraries. The results of the study are discussed in terms of their implications for the future of reference services and the education and training needs of reference librarians. Originality/value: From the results of this study, coupled with data gathered from the review of international literature, it is possible to identify trends and issues influencing reference services and collections.